Democracy and Ethnic War - Mann, Michael (Hagar: Studies in Society and Culture, 2000)
Focussing on ethnic wars, this paper empirically challenges two common, linked assumptions: that democracies are inherently pacific, and that ethnic cleansing is launched by authoritarian rather than elected and quasi-democratic regimes. These false assumptions ultimately derive from liberalism’s misperception of itself. ‘Liberal peace’ prevailed only in unusual historic settings, mostly found in northwestern Europe, where the main lines of exploitation within each state were along class lines and where there was little international exploitation between the states. Contrary to the liberal view of liberalism, its peace depended less on individual interest or toleration than on the institutionalization of class and international conflict. Internal peace did not prevail where exploitation was less by class than by ethnicity entwined with international exploitation. In these latter cases, aspirations for ‘rule by the people’ tend to generate an organic rather than a liberal conception of the people, an ethnocratic conception of the state and (in certain circumstances) ethnic wars. Thus, just as liberal peace depended upon the institutionalization of class and international conflict, so ‘ethnic/national peace’ must depend on a corresponding form of institutionalization, of ethnic and national conflict through consociational or confederal means.